The Schistosoma mansoni tegumental-allergen-like (TAL) protein family: influence of developmental expression on human IgE responses. - Colin M Fitzsimmons; Frances M Jones; Alex Stearn; Iain W Chalmers; Karl F Hoffmann; Jakub Wawrzyniak; Shona Wilson; Narcis B Kabatereine; David W Dunne (PLoS Neglected Tropical Diseases)
Background A human IgE response to Sm22.6 (a dominant IgE target in Schistosoma mansoni) is associated with the development of partial immunity. Located inside the tegument, the molecule belongs to a family of proteins from parasitic platyhelminths, the Tegument-Allergen-Like proteins (TALs). In addition to containing dynein-light-chain domains, these TALs also contain EF-hand domains similar to those found in numerous EF-hand allergens. Methodology/principal findings S. mansoni genome searches revealed 13 members (SmTAL1-13) within the species. Recent microarray data demonstrated they have a wide range of life-cycle transcriptional profiles. We expressed SmTAL1 (Sm22.6), SmTAL2, 3, 4, 5 and 13 as recombinant proteins and measured IgE and IgG4 in 200 infected males (7-60 years) from a schistosomiasis endemic region in Uganda. For SmTAL1 and 3 (transcribed in schistosomula through adult-worms and adult-worms, respectively) and SmTAL5 (transcribed in cercariae through adult-worms), detectable IgE responses were rare in 7-9 year olds, but increased with age. At all ages, IgE to SmTAL2 (expressed constitutively), was rare while anti-SmTAL2 IgG4 was common. Levels of IgE and IgG4 to SmTAL4 and 13 (transcribed predominantly in the cercariae/skin stage) were all low. Conclusions We have not measured SmTAL protein abundance or exposure in live parasites, but the antibody data suggests to us that, in endemic areas, there is priming and boosting of IgE to adult-worm SmTALs by occasional death of long-lived worms, desensitization to egg SmTALs through continuous exposure to dying eggs and low immunogenicity of larval SmTALs due to immunosuppression in the skin by the parasite. Of these, it is the gradual increase in IgE to the worm antigens that parallels age-dependent immunity seen in endemic areas.